STUDI FASIES BATUBARA BERDASARKAN KARAKTERISTIK MACERAL PADA DAERAH KLASUAT, DISTRIK KLAYILI, KABUPATEN SORONG, PAPUA BARAT - Restu Tandirerung; Max Santus (INTAN Jurnal Penelitian Tambang, 2022)
This study aims to determine the characteristics of the coal maceral and the Klasuat coal facies which are included in the Klasaman Formation, Salawati Basin, West Papua of Upper Miocene - Pleistocene age. The characteristics of coal maceral can be identified using maceral analysis, vitrinite reflectance value analysis, interpretation of the depositional environment based on Diessel, and Lamberson and Calder diagrams. The methodology applied in this research attempts to expand the research of coal at the local scale in the Salawati Basin, and to determine variations in coal characteristics controlled by differences in the lateral depositional environment. Based on the results of facies reconstruction of the depositional environment using four parameters TPI (Tissue Preservation Index), GI (Gelification Index), GWI (Ground Water Index) and VI (Vegetation Index) and plotted in the Diessel and Calder diagrams, it is found that the Klasuat Coal Layer was deposited in the facies limnic depositional environment.